Participation and Position of Agrarian Sectors in Global Value Chains in Selected Countries in the Central and Eastern Europe - Zdráhal, Ivo; Fannin, J. Matthew (<center>Conference Proceedings Determinants Of Regional Development</center>; No 3 (2022): Conference Proceedings - IX International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/03/019, 2022)
This article investigates the effects of fragmentation of production on the agrarian sectors in selected countries in Central and Eastern Europe (Czech. Rep., Estonia, Hungary, Latvia, Lithuania, Poland, Slovak Rep., Slovenia, Bulgaria, Croatia and Romania) between 1995 and 2018. The participation index and the position index are used to evaluate the form of integration of the agrarian sectors in these countries into global value chains (GVC). The results suggest that most evaluated countries increased participation in GVC through the time period. EU membership led to increasing participation in GVC. Participation in agrarian global value chains has not expanded since the Great Recession. On average, the position of global value chains in these countries is shifting more downstream with a few outliers (e.g. Slovakia, Estonia, Latvia, and Croatia). The growing integration of the agrarian sectors in countries in the Central and Eastern Europe into the GVC increases the influence of the vertical division of labor/tasks and creates a new set of factors influencing the development of agrarian sectors in these countries.